1984
DOI: 10.1136/bmj.289.6437.83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a gluten free product containing wheat gliadin in patients with coeliac disease.

Abstract: organisms treated with co-trimoxazole suggests differences in the clinical activities of these drugs. Amoxycillin alone is limited in its activity against urinary pathogens owing to the frequent presence of /1-lactamases. Martinelli Evaluation of a gluten free product containing wheat gliadin in patients with coeliac diseaseIn coeliac disease a characteristic lesion of the mucosa of the upper small intestine results in malabsorption. Wheat, rye, barley, and possibly oats have been shown to be toxic to patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 3 publications
0
13
0
2
Order By: Relevance
“…This ensures a wide variety of gluten-free products and does not jeopardize the treatment of coeliac disease with inconvenient restrictions. 7 8 Adults 2.5-5 g gluten daily, median (6 months) -Increase in IELs Catassi et al 6 10 Children 100 mg gliadin daily (4 weeks) Asymptomatic Dose-dependent decrease in Vh/CrD, increase in IELs 10 500 mg gliadin daily (4 weeks) Anorexia and pale stools in three Sturgess et al 26 4 Adults 1 g gliadin (4 h) -Decrease in Vh/CrD in 3/4, increase in IELs in all Srinivasan et al 27 2 Adults 500 mg gluten daily (6 weeks) -Decrease in Vh/CrD in two Laurin et al 28 1 24 Open challenge 7 (7) Adults 1 week Small-bowel biopsy No Ciclitira et al 25 Open challenge 10 (10) Adults 6 weeks Small-bowel biopsy Cr-EDTA excretion Abdominal symptoms in some Ejderhamn et al 11 Cross-sectional 11 (11) Adolescents 10 years on average…”
Section: Discussionmentioning
confidence: 99%
“…This ensures a wide variety of gluten-free products and does not jeopardize the treatment of coeliac disease with inconvenient restrictions. 7 8 Adults 2.5-5 g gluten daily, median (6 months) -Increase in IELs Catassi et al 6 10 Children 100 mg gliadin daily (4 weeks) Asymptomatic Dose-dependent decrease in Vh/CrD, increase in IELs 10 500 mg gliadin daily (4 weeks) Anorexia and pale stools in three Sturgess et al 26 4 Adults 1 g gliadin (4 h) -Decrease in Vh/CrD in 3/4, increase in IELs in all Srinivasan et al 27 2 Adults 500 mg gluten daily (6 weeks) -Decrease in Vh/CrD in two Laurin et al 28 1 24 Open challenge 7 (7) Adults 1 week Small-bowel biopsy No Ciclitira et al 25 Open challenge 10 (10) Adults 6 weeks Small-bowel biopsy Cr-EDTA excretion Abdominal symptoms in some Ejderhamn et al 11 Cross-sectional 11 (11) Adolescents 10 years on average…”
Section: Discussionmentioning
confidence: 99%
“…The variable results obtained in different studies are-at least it part-due to the highly variable gluten sensitivity observed among celiac patients [67]. Ciclitira et al [68] showed that patients consuming 1.2-2.4 mg gluten/day during 1 week had already detectable histological changes in the small intestinal mucosa; yet, in another study using the same amount of gluten administered during 6 weeks, histological mucosal changes could not be demonstrated [68]. Kaukinen et al [69] showed that patients that consumed on average 34 mg gluten/day during 8 years did not develop measurable duodenal histological abnormalities, but individuals consuming 34 mg of gluten daily plus 1-2 g of gluten weekly did develop villous atrophy [69].…”
Section: How Much Gluten Is Tolerated By Celiac Patients?mentioning
confidence: 97%
“…On the other hand, according to some studies, wheat‐starch‐based gluten‐free flours are well tolerated and cause no small bowel mucosal deterioration 10–13 . In some challenge studies, small bowel mucosal inflammation has appeared after the ingestion of 5 mg to 5 g of gluten, 14 , 15 whereas, in others, no significant mucosal changes have been observed 16–18 . Due to this discrepancy, controversy persists as to the safety of wheat‐starch‐based gluten‐free products: these have been used for over 30 years in the UK and Scandinavia, but their consumption is discouraged in the USA 19 …”
Section: Introductionmentioning
confidence: 99%